Private Schools for the Poor: Development, Provision, and Choice in India - Baird, E (2009)
Across the developing world, hundreds of millions of students from very poor families attend private school. Given that governments provide free and universal education, in theory, why do low-income citizens in the developing world with very little income pay fees to send their children to private schools in large numbers? While in the developed world, private schools are typically considered to be reserved for the privileged, in the developing world, millions of low-income families send their children to private school. This thesis utilizes a large-N study of states and regions within India, examining independent variables such as government spending on education, political opinion, economic environment, and cultural factors. In addition, nested case studies in Mumbai and Hyderabad trace causal mechanisms driving the development of the low-cost private school sector. In this thesis, I build on the existing literature surrounding education in the developing world by exploring the explicitly political component of this question. I illustrate how the provision and quality of government schools in low-income areas—and political factors shaping the education sector—explain why many low-income parents are choosing private schools. I also examine cultural and economic factors related to the development of private schools, including language and religion. In the end, private school enrollment in the developing world is demand-driven: rather than be passive recipients of charity, parents with little income make active choices to enroll their children in private schools when governments are not meeting their needs. Government policies and other factors determine whether, and when, parents make this choice.